Microbial electrosynthesis of acetate from CO2 in three-chamber cells with gas diffusion biocathode under moderate saline conditions - Paolo Dessì; Claribel Buenaño-Vargas; Santiago Martínez-Sosa; Simon Mills; Anna Trego; Umer Z. Ijaz; Deepak Pant; Sebastià Puig; Vincent O'Flaherty; Pau Farràs (Environmental Science and Ecotechnology, 2023)
The industrial adoption of microbial electrosynthesis (MES) is hindered by high overpotentials deriving from low electrolyte conductivity and inefficient cell designs. In this study, a mixed microbial consortium originating from an anaerobic digester operated under saline conditions (∼13 g L−1 NaCl) was adapted for acetate production from bicarbonate in galvanostatic (0.25 mA cm−2) H-type cells at 5, 10, 15, or 20 g L−1 NaCl concentration. The acetogenic communities were successfully enriched only at 5 and 10 g L−1 NaCl, revealing an inhibitory threshold of about 6 g L−1 Na+. The enriched planktonic communities were then used as inoculum for 3D printed, three-chamber cells equipped with a gas diffusion biocathode. The cells were fed with CO2 gas and operated galvanostatically (0.25 or 1.00 mA cm−2). The highest production rate of 55.4 g m−2 d−1 (0.89 g L−1 d−1), with 82.4% Coulombic efficiency, was obtained at 5 g L−1 NaCl concentration and 1 mA cm−2 applied current, achieving an average acetate production of 44.7 kg MWh−1. Scanning electron microscopy and 16S rRNA sequencing analysis confirmed the formation of a cathodic biofilm dominated by Acetobacterium sp. Finally, three 3D printed cells were hydraulically connected in series to simulate an MES stack, achieving three-fold production rates than with the single cell at 0.25 mA cm−2. This confirms that three-chamber MES cells are an efficient and scalable technology for CO2 bio-electro recycling to acetate and that moderate saline conditions (5 g L−1 NaCl) can help reduce their power demand while preserving the activity of acetogens.